A poorly known rodentlike mammal (Pachyrukhinae, Hegetotheriidae, Notoungulata) from the Deseadan (Late Oligocene) of Argentina. Paleoecology, biogeography, and radiation of the rodentlike ungulates in South America - Reguero, Marcelo Alfredo (2007)
Fil: Reguero, Marcelo Alfredo. División Paleontología Vertebrados. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina